2007
DOI: 10.1093/europace/eum257
|View full text |Cite
|
Sign up to set email alerts
|

Should we use the rate-adaptive AV delay in cardiac resynchronization therapy-pacing?

Abstract: In consideration of the findings of the studies performed to date, the rate-adaptive AV delay should be deactivated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 23 publications
(29 reference statements)
1
29
0
Order By: Relevance
“…Although Scharf et al 25 suggested an increase in AVD during exercise, more recent publications argue against the need for changing the AVD during exercise. 26,27 It is possible that AVD auto-calibration using integrated haemodynamic sensors with the capability of repeated testing will be helpful to identify device settings that account for the varying conditions during daily life.…”
Section: Body Positionsmentioning
confidence: 99%
“…Although Scharf et al 25 suggested an increase in AVD during exercise, more recent publications argue against the need for changing the AVD during exercise. 26,27 It is possible that AVD auto-calibration using integrated haemodynamic sensors with the capability of repeated testing will be helpful to identify device settings that account for the varying conditions during daily life.…”
Section: Body Positionsmentioning
confidence: 99%
“…Abbreviations as in Figures 1, 4, and 6. known about the magnitude of AVD shortening with increased heart rate in heart failure patients and whether AVD should be shortened, kept constant (47,48), or prolonged (49) as heart rate increases. Recent studies suggest that AVD changes during exercise are variable (50).…”
Section: Naqvi Echocardiography In Pacemaker Optimizationmentioning
confidence: 99%
“…3 Whether adaptive AVDs provide an additional benefit over (echocardiographically optimized) fixed AVDs has not been finally clarified; respective studies have produced conflicting results. [4][5][6] Usually, echocardiographic AVD optimization is performed shortly after device implantation in order to identify the "optimal" AVD. However, respective measurements are performed at rest, and it remains unclear whether this also ensures optimized exercise hemodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies in CRT patients have produced conflicting results. [4][5][6] This prospective monocenter study was designed to compare fixed with adaptive AVD programming in CRT devices with respect to exercise hemodynamics using a noninvasive hemodynamic monitor.…”
Section: Introductionmentioning
confidence: 99%